2017
DOI: 10.1504/mejm.2017.083711
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing acceptance of Ar-Rahnu: comparison between private and state Ar-Rahnu providers in Terengganu

Abstract: Many Muslim customers are hesitant to patronise the conventional pawnbroking shops due to the element of interest which is prohibited in Islam. Amid the demand for a shariah-compliant pawnbroking product, the first Islamic pawnbroking was setup by Maidam in Terengganu. The establishment of Ar-Rahnu provides a convenience form of credit financing which is both shariah-compliant and low cost for public to access financing. Since then, there are currently several private Ar-Rahnu providers offering Ar-Rahnu produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Based on the research in Al-Rahnu, it is mentioned that shariah view is seen as an important factor by the customers in accepting Ar-Rahnu. So, it is imperative for Ar-Rahnu operators to increase the level of Syariah practices in the scheme in future (Abdul Rahman and Kassim, 2017). According to Rasmin and Markom (2014), there are two basic principles of Islamic banking, which are riba prohibition (interest-free) and the sharing of profit and loss between the bank and its customers (mudharabah and musharakah).…”
Section: Shariah Viewmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the research in Al-Rahnu, it is mentioned that shariah view is seen as an important factor by the customers in accepting Ar-Rahnu. So, it is imperative for Ar-Rahnu operators to increase the level of Syariah practices in the scheme in future (Abdul Rahman and Kassim, 2017). According to Rasmin and Markom (2014), there are two basic principles of Islamic banking, which are riba prohibition (interest-free) and the sharing of profit and loss between the bank and its customers (mudharabah and musharakah).…”
Section: Shariah Viewmentioning
confidence: 99%
“…There are several advantages of gold as the collateral compared to other pawned items such as that gold can be easily resold, gold's purity is easily determined and the mispricing of the collateral can be minimised, gold chains and rings typically require only a small flat envelope for storage, and women often receive gold chains and bracelets as their wedding gift and retain them for personal ownership (Abdul Razak, 2008). Abdul Rahman and Kassim (2017) expressed that pledge asset is significantly associated with acceptance and it is seen as a crucial factor. According to the study conducted by Azman and Kassim (2015), a few respondents proposed to diversify the mortgaged items.…”
Section: Shariah Viewmentioning
confidence: 99%
See 2 more Smart Citations
“…The religious compliance factor is also the main issue that Muslim users often consider when choosing al-rahn, and previous studies have reported 48.2% of respondents chose alrahn because of religious factors when al-rahn were implemented in accordance with Islamic law [15]. Other studies that agree on the importance of religious factors in the implementation of al-rahn are Amin Rahman and Kassim (2017) found that the influence of religion has the lowest correlation value due to the diverse religious backgrounds in Sarawak. This is because awareness of an individual towards al-rahn is different according to religion.…”
Section: Literature Reviewmentioning
confidence: 99%